"A footstool of war, honour and shame?" perspectives induced by Psalm 110:1 - Sutton, Lodewyk (Journal for Semitics, 2016)
One of the key concepts and metaphors in Psalm 110:1 is the concept of "the enemy made a footstool". The war language is especially illustrated by the imagery of the footstool, where the warfare function or purpose can be expressed through the concepts of honour and shame. To gain a better perspective on the meaning and use of this imagery it is first indicated why the imagery of the footstool can be considered as part of war language and imagery (part of warfare). Secondly, the role of honour and shame as an expression of the function and purpose of the war language and imagery is made through a social-scientific analysis of the footstool. Thirdly, iconography of different ancient Near Eastern (and Mediterranean) contexts is used as an extratextual source to elucidate the concept of the footstool in its use of war language and imagery as further expressed through the concepts of honour and shame. Lastly, the use of footstool in Psalm 110:1 is examined and applied. This identifies the footstool in Psalm 110:1 as "a footstool of war, honour and shame".
free